Refined balance of propulsive forces - Kleshnev, V. (BioRow, 2021)
The main achievement of this study was to obtain the refined balance of propulsive forces in the rower-boat-oar system, which confirms the validity of our models, accuracy of the measurements, and allows further extended studies and optimisation of rowing biomechanics.